KONSTRUKSI MAKNA “DUGEM” BAGI MAHASISWA PELAKU DUGEM DI KOTA PEKANBARU - Gatot Dirgantoro; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
World Glamor or Dugem for teenagers became a phenomenon that became a trend in the past. The perpetrators Dugem many from various circles, especially the yatiu students. Until now dugem trend is so growing with ditandainya the increasing number of nightspots in Pekanbaru City which was established from the center of the city to the remote areas. The glittering world, of course, is very close to alcohol and drugs so they get negative awareness by the people. This study aims to determine the motives, meaning and experience of student communication in Pekanbaru Pekanbaru dugem.This study uses a qualitative study method with a phenomenological approach. Informant investigation consisted of six students dugem players in the city of Pekanbaru selected using snowball technique. Techniques of data collection methods of attention, in-depth interviews, and investigation documentation. To achieve the validity of the data in this study, investigators use continued triangulation participation, and the adequacy of referrals.The result of the study shows that first, the dugem motive for the students of the dugem in Pekanbaru City consists of the motive because of the hobby of music, the trend of dugem, the influence of the friend, and the job networking, while the motive for (in order to motive) ie stop to do dugem, became a life experience and changed the negative outlook on the dugem. Second, the meaning of dugem yes by Student actors dugem iaitu dugem as life experience, dugem as a place to add relations, and dugem as a breakout problem and relieving stress. Third, the communication experience of dugem actors are categorized into two namely verbal pleasant communication experience in the form of support of parents to their children to follow dugem and the invitation and support from friends and friends to do dugem, and not verbalnya in the form of entertaining friends dugem there in clubs with rocking, and the presence of symbols and sign language to pick up dugem. uncomfortable communication experience verbal in the form of blasphemy from the surrounding environment against the perpetrators of dugem and in the form of a loud reprimand with the words of the parents and punishment of the perpetrators dugem, and not verbnya in the form of rape in the club because the drunken clubbers.